The effect of pro-self-pain control and its plus guided imagery on pain in breast cancer outpatients: A quasi-experimental study - Nurnianingsih A. Yasin; Rosyidah Arafat; Andi Masyitha Irwan (Nursing Practice Today)
Background & Aim: Globally and in Indonesia, the number of people with breast cancer is still rising, and one of the most commonly reported symptoms is pain. After hospitalization, patients continue their lives at home, and most receive care in an outpatient setting. In this setting, they voluntarily need to be able to manage their pain. Therefore, teaching and assisting patients in self-management is essential for adequate pain management. This study aims to determine the effect of pro-self-pain control and guided imagery interventions on reducing pain intensity in outpatient breast cancer. Methods & Materials: A quasi-experimental design, using convenience sampling on 49 patients, and allocated into an intervention group (n=25) that received pro-self-pain control and guided imagery intervention and a control group as a comparison (n=24) that received pro-self-pain control only. Pain intensity in both groups was measured before the experiment and ten days after using the Numeric Rating Scale. Results: The results showed that there was a significant decrease in pain intensity in the intervention group p<0.001. The control group also experienced a decrease in pain intensity, but not significant p=0.212. Before the intervention, both groups showed no significant difference (p=0.872). However, after the intervention, the difference test between the two groups showed a significant difference with a p=0.004 and a small effect size (d=0.40). Conclusion: The combination intervention of Pro-self-pain control and guided imagery (with audio recordings) effectively reduces pain intensity, although the effect size produced tends to be small. In caring for cancer patients, it is recommended to improve health education regarding pain management, thereby enabling them to self-manage their pain and participate actively in controlling it.